Benefits of Green Spaces and Physical Activity for the Well-Being and Health of People [Beneficios de Los Espacios Verdes y Actividad Física en el Bienestar y Salud de Las Personas] - Cortinez-O'Ryan, A (Sociedad Medica de Santiago, 2022)
Background: Physical environment can influence well-being, quality of life and health and population health in several ways. Exposure to green spaces improves the physical and mental health of individuals. Chile has privileged conditions for outdoor activities that could benefit millions of people. However, a small percentage of the Chilean population is exposed to green spaces in the recommended amounts to promote health. Aim: To describe the benefits of green spaces on physical and mental health and their relationship with the practice of physical activity. Material and Methods: Review of the scientific literature in English in the Web of Science (WoS) electronic database published between 2006-2019. Results: In addition to the direct benefits of green spaces, there are synergistic effects of performing physical activities in these environments such as feelings of good health, satisfaction with life and pleasure, increased physiological relaxation, positive emotions, mental well-being, restoration of attention, decreased perceived stress and a reduction negative affections. Conclusions: This review supports strategies for improving access to green spaces in urban areas coupled with physical activity promotion in these settings. Health and urban planning stakeholders should consider these aspects in future programs. © 2022 Sociedad Medica de Santiago. All rights reserved.